Αγγλικά - Simple Present & Present Continuous - Δ'-Ε' Δημοτικού Επ. 85 (Υπουργείο Παιδείας και Θρησκευμάτων, 2020)
: [♪ Μουσική' Good morning! My name is Cecilia. Θα σας κάνω σήμερα Αγγλικά. Θα ξεκινήσουμε από κάποιους βασικούς κανόνες της γραμματικής. Μην αγχώνεστε που θα σας μιλάω αγγλικά. Θα μιλάω σιγά σιγά ώστε να με καταλαβαίνετε όλοι. Και στο ενδιάμεσο θα λέω και κάποιες ελληνικές λέξεις, αλλά listen in English. Ok, so today we are going to learn simple present and present continuous. So, these are two very important tenses. And you have to understand their differences. Έχουν κάποιες πολύ βασικές διαφορές που θα αναλύσουμε. Ok, so let's start from the very beginning. Λοιπόν, ο simple present έχει το affirmative. Αφέρμαρευ είναι η κατάφαση. Πώς κλείνουμε το simple present in the affirmative. Θα φτιάξουμε εδώ δύο στήλες. Simple present and then present continuous. Ok, so let's start from a basic verb, like I play. Πώς κλείνεται στο affirmative. Affirmative is κατάφαση. So, let's take all the I, you, he, she, it and then we have we, you and they. So, in the simple present what we do is we write I play, you play and he, she and it plays. So, we add S in the end, right? You know this, you have learned this, I'm just reminding you. So, we add S in the end. And then in the plural again, we play, it stays the same, you play, they play. So, this is how you conjugate a verb. Careful, only after he, she and it, you add S. Ok, these are the basic rules of simple present. Now, there are some exceptions, υπάρχουν κάποιες εξαιρέσεις. Only here, στο he, στο she και στο it. Some spelling rules that we need to learn. Number one, I will write it on the board, για να τα έχετε. Λοιπόν, number one, όπως είπαμε, we only put S, στο he, στο she και στο it. Number two, I will show it to you on the screen later, so θα τα δείτε κιόλας. When the verb, όταν το ρήμα τελειώνει, ends in sh, ch, s, x and o, what do we do? We don't put S, δεν βάζουμε S μόνο, we put es, στο τέλος, in the end. We only put es. So, let's see some examples. Let's take the verb brush. Ok, so, what happens? I brush, you brush, he, she, it brushes, do you see? So, es, not only s. Or let's say, watch. I watch, I watch TV, right? I watch, you watch, he, she, it watches. Ok, now, I pass, I pass, you pass, he, she and it passes. Ok, then let's say, I fix, with an x, again, he, she and it fixes. Ok, and finally, I do. I do, you do, he, she, it does. So, this is the second basic rule. What we do is we put es in the end. And then the third one, which is also very important, is when a verb ends in a consonant and y, now, what is a consonant? Consonant is σύμφωνο, in Greek. So, all the letters, except A, I, E, O and U, those are five vowels. All the other letters are consonants. So, let's say, if we have a consonant plus y, ok, we take out the y and we put i, e, s. So, for example, I study, you study, he, she, it, we take the y, ok, we erase it and we put i, e, s. Studies, ok? Now, careful, if before, before the last, ok, the last letter, we don't have a consonant and we have a vowel, so we have A, I, E, O and U, we don't change it, like play. Look at this, play has a vowel before y, not a consonant, so we don't change it, we just put s, like before. So, these are the three basic spelling rules of simple present. We've got s, only in he, she, it, everything changes. Ok, we've got e, s and i, e, s. Ok, so let's remember these, you know them already, I'm just telling you again so you can remember everything. Now, let's go to present continuous. What happens here? Here it's a little bit different. What we do is, we take the verb to be, the verb to be is I am, you are, he is, etc. Let's start, again the affirmative. So, I am, you are, he is, she is, it is, we are, you are and they are. So what do we do over here? We take this verb and then we put ing. So, let's take again the verb play. What do we do? We write I am, play and then ing, playing, ok? Again, you are, playing, I'm not going to write it again, it's everywhere the same, he is playing, she is playing, it is playing, we are playing, you are playing, they are playing. It doesn't change anywhere. The only thing we do is we change here, the verb to be, ok? Now, there are two ways to do this. There's the short form and the long form. This is the long form, ok? It takes a while. If you're bored, you can change it and you can erase a. I'm playing, ok, this is the short form. You are, you are playing. We erase the first letter. He, let's just do it all together. There, and it's gone. He's playing, she's playing, it's playing, we're playing, you're playing and they're playing. So basically, this is the short form. We usually use this just because it's faster. I have an example, you will see it in your screens. Θα το δείτε και εκεί πως γίνεται και στο short και στο long form, ok? Now, let's go back. Spelling rules. So again, let's remember the spelling rules of present continuous in the affirmative. The first rule, ok? We just said, add img to the verb in the end. So, play, playing. Let's do play here again. I'm playing. Ok? First and important rule. Number two. When the verb ends with a silent e, like, let's say silent e, ok? Like make or take, we erase the e and again we add img. So, let's say, I'm, make, making. Do you see it like this? We can't do it like this with two vowels, one next to the other here. We erase the e, so it becomes I'm making. Ok? Or take. I'm, take, we erase the e, ing, taking. Ok? So, this is the second important spelling rule. Now, this is the most difficult one, but if you understand it, if you listen carefully, it's not that difficult. Now, when we have a verb, ok, that ends in consonant-vowel-consonant and it has to be stressed, we double the last letter. What did I say now? Let me explain again. So, when we have consonant-vowel-consonant, we double the last one, the last letter. Look at here, this stop. Ok? Consonant-vowel-consonant. Ok? So, what do we do? We double p, the letter p, the last letter of the verb. So, stop becomes I'm stopping. So, you see? Two p's. Ok? This is very important, so careful. Let me. Stopping, double p. Or, let's say, begin. I'm beginning. Begin, double n. We put two n's. Now, I think it's easier for you to understand. I'm beginning. So, it ends with a consonant-vowel-consonant and it's stressed. Begin. So, what am I saying here? Let me say it in Greek quickly. Όταν έχουμε ένα ρήμα που τελειώνει σε σύμφωνο-φωνήεν και σύμφωνο και πρέπει να τονίζεται κιόλας, δηλαδή begin στο τέλος, διπλασιάζουμε το τελευταίο γράμμα. Ok? So, stop, stopping. Begin, beginning. So, you do it twice. Ok? This is basically what I meant. And the fourth one. Ok? The verbs that end in IE, in the end, ok, we take out the IE and we put Y. So, let's see. The verb tie, ok, and lie. What do we do over here? I'm tying. We erase the IE and we put Y. Now, it's not very straight, ok, but you understand. Lie. I'm lying. Next. Ok? So, you understand basically what happens over here. We take out the I and the E and we put Y. So, I have it again in your screen. You can see it. Let's remember one more time. In simple verbs we just put I and G. Ok? Then, when the verb ends in E, we put I and G and we take out the E. When the verb ends in a stressed consonant, vowel consonant, we double the last letter. And then when it ends in I and E, we erase the I and E and we put a Y. Ok? So, these are the basic spelling rules again of present continuous. So, let's erase everything. And now, we will learn the negative. How do we form the negative of both of these tenses? It's much easier and you don't need to learn a lot of things. So, in simple present, how do we form the negative? So, let's write here negative. Ok. We take again I, you, he, she, it, we, you and they. Ok. Let me use the red this time. And we put the this don't. I don't. Ok. You don't. He, she and it again always they have their own doesn't. Ok. And then we don't. You don't. They don't. Ok. So, this is how we form the negative in simple present. And then the verb stays the same. You don't do anything. I don't play. You don't play. Careful. We don't do he doesn't plays. Right? Uh-uh. Play. Same. We don't play. You don't play. And they don't play. So, we only conjugate this. This stays the same. This is how we form the negative in simple present. Now, what about present continuous? So, again, again we have the long form and the short form. We usually use the short one, but let's learn both of them. So, the long one is I am not playing. Ok. Again, we conjugate the verb to be. You are not playing. He is not playing. The same goes for he, she, is, it is. Again, it's the same, not playing. I and G in the end. So, careful. It's the same. And then we are not playing. You are not playing. And finally, they are not playing. So, this is the long negative form. It's the long one. You will learn the short one. It's easier. In the short form, you just do I'm not playing. You, what do we do over here? We erase this. You aren't. How do we make this? We just erase the O. And you put, you make it one. For example, is not. Let's erase the O. Isn't. And then you connect it. So, let's do it again. Isn't. Ok. Then again, let's erase the O. I'll erase all of it. Isn't. Again, isn't. We aren't. You aren't. They aren't. And then we connect them basically. Like we did over here. So, this is the short form. I'm not. You aren't. He isn't. She isn't. It isn't. We aren't. You aren't. And they aren't. It's in, I will show it again in your screen. You can see it over there. I don't need to write it again. It will take too long. So, you can all see it in your screen. Now, the interrogative. The interrogative, η ερώτηση. In simple present, what do we do? Again, you can see their differences. That's why I put them together. Να βλέπετε τη διαφορά του simple present και του continuous. In simple present, it's do I, do you, play of course. And then it changes in he, she and it. You just put does in front. So, does he, does she, does it, play. Play always stays the same. So, you never change it. It's very simple. So, I just showed it to you quickly. And then the interrogative in present continuous is am I. So, you take I am playing and you reverse it. And it becomes am I playing? Are you playing? Is he playing? Is she playing? Is it playing? And then again, are we, are you, are they playing? So, again, nothing changes over here. You change it here. Okay? So, these are the basic rules of how to form these tenses. Now, when do we use them? Okay? When do we use simple present? When do we use present continuous? So, simple present. Simple present is habits, routines and general truths. Είναι για συνήθειες, για τη ρουτίνα, τι κάνουμε κάθε μέρα και γενικές αλήθειες. For example, I live in Athens. Μια γενική αλήθεια. Or, fish swim in the ocean. Or, you can say, I go to school every day. So, it's part of your routine. Okay? Simple present. Now, present continuous is something that happens now. Κάτι που γίνεται αυτή τη στιγμή. For example, right now, I am teaching. Okay? Or, you are sitting on your couch. So, it's happening now. Now, this is the first use they have. Number two about simple present is for a permanent situation. Μια μόνιμη κατάσταση. For example, I am a teacher. I teach English. Always. This is my permanent situation. Or, I am a painter. I paint beautiful paintings. Now, present continuous is for a temporary situation. So, something that's happening only for today. Or, only for this week. For example, I teach English every day. But, today I am sleeping. So, we use present continuous because it's happening only for today. Not every day. Okay? And, the third important use, simple present is for timetables. Timetables are τη ώρα φεύγει το λεωφορείο, το αεροπλάνο. For example, the bus leaves at 9. Το λεωφορείο φεύγει στιγμή. You use simple present. But, present continuous, this is important, is used for future plans. Όταν έχουμε σχεδιάσει να κάνουμε κάτι στο κοντινό μέλλον. For example, tonight I am watching a movie with my friends. Or, tonight I am making pizza. So, it's something that will happen στο κοντινό μέλλον, in the near future, because you have planned it. Το έχεις σχεδιάσει να γίνει οπωσδήποτε. Okay? So, these are the three basic rules about when we use these tenses. And, finally, time expressions. Okay? Words that will help you use these tenses. So, when you see them, you know, I am going to use simple present. Or, I am going to use present continuous. These are on your screen. So, θα τα δείτε και στην οθόνη σας. In simple present, we use expressions like every day, every week, every month. Or, on Monday, on Tuesday. And, of course, the adverbs of frequency. Τα παιδίματα συχνότητας. So, always, I always go to school. Or, I usually go to school. Αυτά είναι τα always, usually, often, sometimes. There are many. Το never. So, we use simple present with these. And, present continuous, of course. Now, right now, at the moment, or today, these days. So, κάτι που δείχνει κάτι που δεν είναι μόνιμο και permanent, προσωρινό. Okay? So, this is also on your screen. You can see this and maybe write it down. Or, I don't know, you can learn it by heart. So, these are the basic rules that I taught you today. I hope you understood them. And, ό,τι χρειάζεται, you can watch it again, you can pause it, you can take notes. I hope I really helped you. I hope you have a nice day.